The deficit of formulation of the public policy of the national road infrastructure of 1998 - Vásquez Rodríguez, Jorge Alberto (2025)
The reorientation of the public policy of the national road infrastructure of 1998 incorporated key aspects of the New National Style of Development in force in the country at the time of its officialization. Since the beginning of the 1980's, this style promulgates the leading role of the market, in deterioration of the role of the State, hence, in accordance with it, the construction, conservation and maintenance of the National Road Network of the State was transferred to the private entrepreneur, through contracts administrative tasks in charge of a public entity called the National Highway Council, where three members of the organized businessmen of the highway construction market would be incorporated into its administrative council, with voice and vote. They would co-manage the institution, with three other members representing the current government and one from the local governments, with resources from a National Road Fund. The formulation of the policy holds a deficit, generated mainly by the reformulation of the public problem and the intervention strategy of the public policy, generated from “the political” in the Legislative Assembly in the first quarter of 1998. Hence, a possible response was not provided to some of the causes of the public problem, such as the relocation of services, expropriations, coordination with public entities that determine the progress of road works, environmental protection, control and quality of highways, excessive control over road works, exercised directly or indirectly by controlling public entities, thus generating a formulation deficit in public policy, which negatively affects its results.